2005
DOI: 10.1128/iai.73.12.8345-8352.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant ofFrancisella tularensisStrain SCHU S4 Lacking the Ability To Express a 58-Kilodalton Protein Is Attenuated for Virulence and Is an Effective Live Vaccine

Abstract: Francisella tularensis subsp. tularensis (type A) strain SCHU S4 is a prototypic strain of the pathogen that is highly virulent for humans and other mammals. Its intradermal (i.d.) 50% lethal dose (LD 50 ) for mice is <10 CFU. We discovered a spontaneous mutant, designated FSC043, of SCHU S4 with an i.d. LD 50 of >10 8 CFU. FSC043 effectively vaccinated mice against challenge with a highly virulent type A strain, and the protective efficacy was at least as good as that of F. tularensis LVS, an empirically atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
251
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(267 citation statements)
references
References 30 publications
13
251
0
1
Order By: Relevance
“…F. tularensis is known for its ability to proliferate within the macrophages of mice and humans. In fact, this is one of the few established properties that contribute to the virulence of the organism, as mutants lacking a gene required for intra-macrophage growth are avirulent in mice [7,8,10]. Others have shown that an LpnA-deficient strain of F. tularensis subspecies novicida replicates 10-fold less in the murine macrophage-like J774 cell line than does its parental strain [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F. tularensis is known for its ability to proliferate within the macrophages of mice and humans. In fact, this is one of the few established properties that contribute to the virulence of the organism, as mutants lacking a gene required for intra-macrophage growth are avirulent in mice [7,8,10]. Others have shown that an LpnA-deficient strain of F. tularensis subspecies novicida replicates 10-fold less in the murine macrophage-like J774 cell line than does its parental strain [47].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of this organism to replicate to high numbers in murine macrophages, as well as to cause fatal disease in mice, is associated with IglC, a 23-kDa protein that is highly expressed during intramacrophage growth [5][6][7][8]. Mutation of the pdpA and pdpD genes of F. tularensis subsp.…”
Section: Introductionmentioning
confidence: 99%
“…tularensis. A recent report was the first to show that site-directed mutagenesis of strain Schu S4 is possible, using a conjugative sacB plasmid encoding chloramphenicol resistance (Twine et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The FslE paralogs are unique to Francisella species, although they show some variation among the different strains. The paralog with the greatest similarity, FupA was initially characterized as a virulence factor in Schu S4 based on attenuation of a fupA mutant in a mouse model of tularemia (27). fupA was found to be important for intracellular replication of Schu S4 as well as F. novicida (23,27), and the related fupA/B hybrid protein in LVS has also been linked to virulence in mice (28).…”
mentioning
confidence: 99%